Digital Workflow in the Analysis of Orofacial Cleft in Children: Case Series with 5 Years of Follow-Up - Ambrosio, Eloá Cristina Passucci; Camargo, Patrícia Bassani; Jorge, Paula Karine; Carrara, Cleide Felício Carvalho; Machado, Maria Aparecida Andrade Moreira; Oliveira, Thais Marchini (ARCHIVES OF HEALTH INVESTIGATION, 2023)
An objective was detailed the digital workflow steps to analyze dental arch of children with cleft lip and palate. Five children underwent impressions of the upper dental arches in the following stages: Stage 1 – before lip repair (3 months of life); Stage 2 – after lip repair/ before palate repair (12 months of life); Stage 3 – after palate repair (24 months of life); and Stage 4 – with early complete/ mixed deciduous dentition (from 5 years of age). After the impressions, dental casts were made with orthodontic plaster, and trimmed to obtain standardized dentoalveolar bases. Dental cast digitalization was performed using a 3D scanner coupled to a computer. Using stereophotogrammetry system software, anatomical landmarks were delimited for the evaluation of linear measurements, palatal surface area, volume, and dental arch superimposition. It is concluded that, the digital analysis of dental arches represents a significant change in the diagnostic process and treatment planning of children with orofacial clefts. The multiplicity of equipment and software guarantees reliable, reproducible, and valid tools for use in clinical practice and in scientific research.